Caralluma Diffusa (wright) N.E. BR. (Apocynaceae) - A New Distribution Record for Kerala from Chinnar Wild Life Sanctuary, India - Kumar, K. M. Prabhu; George, Satheesh; Sreedhar, Sreekanth; Balachandran, Indira (Indian Forester, 2013)
Caralluma diffusa (Wright) N. E. Br. Is reported for the first time from Kerala, Chinnar Wildlife Sanctuary. The current paper provides the description and a detailed key of Indian Carallumas along with colour plate of this species.